사업자단체의 금지행위와 부당성 판단 - 대상판결: 대법원 2021. 9. 9. 선고 2016두36345 판결 - - 나지원 (경쟁법연구, 2022)
Recently, Supreme Court has revoked the disposition of Korea Fair Trade Commission(hereafter “KFTC”). While KFTC determined that the shutdown resolution of Korea Medical Association violated article 26 of the Monopoly Regulation and Fair Trade Act(hereafter “MRFTA”), Supreme Court viewed that KFTC failed to prove the restraint of competition required in MRFTA Article 26 (1). (i) and (iii). This article intends to analyze the Supreme Court’s rulings on prohibited acts of trade association pursuant to Article 26 (1). (i) and (iii) of MRFTA and ‘undue’ restraint of business activities against its members. Although the Court have declared that the word ‘undue’ in Article 26 (1). (iii) means restraint of fair and free competition, it is still not clear that what the restraint of competition actually means. This case review includes recent Supreme Court jurisprudence and the precedent case of the 2003 Supreme Court(en banc). Both cases dealt with similar situations. This review intends to compare and analyze the jurisprudence of the Supreme Court on undue restraint of business by trade association in two cases. The jurisprudence of the Supreme Court is expected to greatly affect the enforcement of MRFTA and its basic principles. Since the business contents and activities of undertaking members are restricted by the resolution of the trade association in due course, Article 26 (1). (iii) aims to prohibit the restriction only when the restriction is undue. The criteria for judging “undue” in Article 26 (1). (iii) should be determined by comprehensively considering the relationship with restrain of competition in a broad perspective and the purpose of the MRFTA.
Keywords: 사업자단체; 구성사업자; 부당한 공동행위; 부당한 사업활동 제한; 경쟁제한성; trade association; undertaking members; cartel; undue restraint of business; restrain of competition